Nafamostat mesilate attenuates inflammation and apoptosis and promotes locomotor recovery after spinal cord injury - Duan, Hui‐Quan; Wu, Qiu‐Li; Yao, Xue; Fan, Bao‐You; Shi, Hong‐Yu; Zhao, Chen‐Xi; Zhang, Yan; Li, Bo; Sun, Chao; Kong, Xiao‐Hong; Zhou, Xin‐Fu; Feng, Shi‐Qing (CNS neuroscience & therapeutics, 2018)
Summary Aim Spinal cord injury (SCI) leads to severe neural damage for which there is currently no effective treatment. Exploration of the neuroprotective effect among clinically approved drugs will speed up clinical translation of SCI. Nafamostat mesilate (NM) as a synthetic serine protease inhibitor has been used clinically in pancreatitis treatments. However, its effectiveness in SCI is unknown. The aim of this study was to confirm the efficacy of NM in ameliorating SCI. Methods Intraperitoneal administration of NM was performed on a contusion SCI model in Wistar rat. Hematoxylin and eosin staining (H&E staining) and Luxol fast blue (LFB) staining were used to observe the histological lesions. Apoptosis was examined by TUNEL staining, Annexin V‐FITC/PI, caspase‐3, and Bcl‐2. Cytokines and neurotrophins were tested by Western blot. Locomotion recovery assessed by hindlimb BBB score and the inclined plane test. Results Nafamostat mesilate treatment significantly improved locomotion recovery as assessed by hindlimb BBB scores and the inclined plane test. H&E staining and LFB staining showed a significant increase in spared tissue in both gray matter and white matter. NM decreased the expression of the proinflammatory cytokines TNF‐α and IL‐6. In addition, apoptosis was also significantly decreased, as shown by TUNEL staining and Annexin V‐FITC/PI and by Western blotting for caspase‐3 and Bcl‐2 expression. Due to the mechanism of action of NM as a serine protease inhibitor, the drug decreased thrombin expression in the damaged spinal cord. Furthermore, NM increased the expression of neurotrophins (NT‐3, BDNF, and NGF). Conclusions Upon NM treatment, the functional and histological outcomes were improved, and microenvironment upon SCI was modulated. As a clinically approved drug, NM holds promise for clinical use after spinal cord injury.